Gone in 60 seconds [videorecording (DVD)] - Halicki, H. B., 1940-1989; Halicki, H. B., 1940-1989; Jones, Parnelli, 1933-; Busia, Marion; Daugirda, Jerry (Mill Creek Entertainment, 2019)
A retired master car thief must come back to the industry and steal fifty cars with his crew in one night to save his brother's life.